Macrophage-tropic HIV-1 variants from brain demonstrate alterations in the way gp120 engages both CD4 and CCR5 - Salimi, H.; Roche, M.; Webb, N.; Gray, L.; Chikere, K.; Sterjovski, J.; Ellett, A.; Wesselingh, S.; Ramsland, Paul; Lee, B.; Churchill, M.; Gorry, P. (2013)
BR-derived HIV-1 strains have an exceptional ability to enter macrophages via mechanisms involving their gp120 Env that remain incompletely understood. Here, we used cell-based affinity-profiling methods and mathematical modeling to generate quantitative VERSA metrics that simultaneously measure Env-CD4 and Env- CCR5 interactions. These metrics were analyzed to distinguish the phenotypes of M-tropic and non-M-tropic CCR5-using HIV-1 variants derived from autopsy BRs and LNs, respectively. We show that highly M-tropic Env variants derived from brain can be defined by two distinct and simultaneously occurring phenotypes. First, BR-derived Envs demonstrated an enhanced ability to interact with CD4 compared with LN-derived Envs, permitting entry into cells expressing scant levels of CD4. Second, BR-derived Envs displayed an altered mechanism of engagement between CD4-bound gp120 and CCR5 occurring in tandem. With the use of epitope mapping, mutagenesis, and structural studies, we show that this altered mechanism is characterized by increased exposure of CD4-induced epitopes in gp120 and by a more critical interaction between BR-derived Envs and the CCR5 N-terminus, which was associated with the predicted presence of additional atomic contacts formed at the gp120-CCR5 N-terminus interface. Our results suggest that BR-derived HIV-1 variants with highly efficient macrophage entry adopt conformations in gp120 that simultaneously alter the way in which the Env interacts with CD4 and CCR5. © Society for Leukocyte Biology.